Pembuatan Gel Pengharum Ruangan Menggunakan Karagenan Dan Xanthan Gum Dengan Minyak Nilam Sebagai Fiksatif Dan Minyak Kopi Sebagai Pewangi - Humaira, Ziaul; Suryani, Suryani; Munawar, Munawar (Jurnal Riset, Inovasi, Teknologi & Terapan, 2022)
The manufacture of air freshener gel using carrageenan and xanthan gum with patchouli oil as a fixative and coffee oil as a fragrance has been carried out, with carrageenan and xanthan gum content contained in a ratio of 30:70, 40:60, 50:50, 60:40 and 70:30as a gel base. With the addition of coffee oil which has a concentration variation of 1%, 2%, 3%, 4% and 5%. This study aims to determine the effect of variations in the composition of the mixture of carrageenan and xanthan gum on the characteristics of air freshener gel, patchouli oil as a fixative and coffee as a fragrance. From the best results, it was found that the best characteristics were found in G4 with ratio of carrageenan and xanthan gum 60:40. From the result of organoleptic test, it was found that the most preferred oil concentration was K3 with 5% coffee oil concentration. From the result of the liquid evaporation test at room temperature, the best result were N1 with 1% patchouli oil concentration, in the fan room the best results were N4 with 4% patchouli oil concentration and in the AC room the best results were N4 with 4% patchouli oil concentration. Meanwhile, the best fragrance resistance test results were found in N3 with a concertation of 3% patchouli oil